APPLICATION OF MY HEALTH REPORT BOOK THE HEALTH INFORMATION SERIES WITH A COMBINATION COUNSELING INCREASED THE HEALTH KNOWLEDE OF SCHOOL STUDENTS IN SIBOLGA - Bibi Ahmad Chahyanto (Jurnal Vokasi Kesehatan, 2020)
Currently, there are still many health and nutrition problems on adolescents in Indonesia. Efforts made by the government to improve adolescent health in schools through the My Health Report Book. Since its launch and distribution to students, until now the application of this book has not been optimal. This study aims to determine the impact of the use of the My Health Report Book Health Information series (RK Book series) combined with counseling to increase student health knowledge. The study design used was quasy experimental with one group pretest-posttest design. There were 82 students who were respondents, consisting of three classes in SMP Negeri 1 Sibolga. Respondents were given an intervention in the form of using the Infokes RK Book Series combined with health education. Counseling was done three times with the distance between the counseling was one week. Pretest and posttest were given one week before and one week after the intervention period. The results of the study prove that respondents consisted of 41.46% of men and 58.54% of women between the ages of 11-14 years. Most respondents (78.04%) had normal nutritional status (BMI/U). There was a significant difference between the level of knowledge and attitudes related to the health of respondents before and after the intervention. The conclusion of this study was the use of Infokes RK Book series combined with health education can improve the health knowledge of school students.